Crack in the press: journalism’s representations and imaginary of the advent and explosion of the drug in Belo Horizonte (MG, Brazil) - Bruck, Mozahir Salomão (Brazilian journalism research, 2013)
This article reports research results from an investigation into the coverage given by the Estado de Minas newspaper – reputed to be a leading opinion maker in the state – on crack usage and commerce in Belo Horizonte, the state capital. Theoretical references adopted originated from social sciences and, in particular, from the theories of journalism. In the research, which covered 15 years the daily newspaper Estado de Minas issues, the analytic content configured the constitution of the corpus, as well as its analysis and interpretation. The aim was to understand the way journalism portrays the underworld of crack and refers to the drug, to its actors, and to its complex networks of distribution, usage, power struggles, prevention and treatment. The objective based on the assumption that, in one way or another, the perceptions engendered by the journalistic discourse effectively have an impact on the society in which the discourse circulates.